​​​The impact of sedentary behavior on blood glucose levels in type 2 diabetes mellitus patients: A literature review - Damayanti, Lelyana Septia (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Sedentary behavior, characterized by prolonged sitting or lying down, is increasingly recognized as a major health risk, particularly for individuals with type 2 diabetes mellitus (T2DM). Previous studies have shown that sedentary lifestyles can exacerbate glucose control issues, leading to poor glycemic regulation and an increased risk of complications. This study aims to explore the relationship between sedentary behavior and blood glucose levels in T2DM patients, highlighting the potential benefits of interrupting sedentary time with physical activity. Methods: This research utilized a comprehensive literature review methodology, analyzing studies published over the past decade to assess the impact of sedentary behavior on glycemic control in T2DM patients. The review focused on both observational studies and experimental trials, employing data from clinical studies and patient monitoring. Findings: Prolonged sedentary behavior was found to be associated with worsening glucose control, including prolonged hyperglycemia and reduced euglycemia. Interrupting sedentary time with short bouts of physical activity (e.g., walking or light exercise) was shown to significantly improve glucose uptake in skeletal muscles, providing effects similar to anti-diabetic medications. Consistent and frequent interruption of sedentary behavior resulted in improved daily blood glucose control, potentially offering a non-pharmacological intervention for T2DM management. Conclusion: The study underscores the importance of reducing sedentary behavior in T2DM patients as a strategy to enhance blood glucose control and prevent complications. Regular physical activity interruptions can serve as a critical non-pharmacological intervention to manage and control blood glucose levels. Novelty/Originality of this article: This review contributes to the growing body of evidence on the health risks of sedentary behavior in T2DM patients, emphasizing the potential of simple lifestyle interventions to improve glycemic control, which has been insufficiently explored in previous literature.